Comparing international postgraduate training and healthcare context with the UK to streamline overseas GP recruitment: four case studies. Issue 3 (August 2020) - Fletcher, Emily; Campbell, John; Pitchforth, Emma; Freeman, Adrian; Poltawski, Leon; Lambert, Jeffrey; Hawthorne, Kamila
No abstract available